Bioinformatics-based identification of SPNS3 (Spinster homolog 3) as a prognostic biomarker of apoptosis resistance in acute myeloid leukemia. Issue 1 (1st January 2021) - Hong, Yang; Tian, Xiaopeng; Wang, Mengmiao; Chen, Cheng; Sun, Aining
ABSTRACT: Spinster homolog 3 (SPNS3) belongs to the Spinster (SPNS) family which participates in sphingolipid transportation through the cell membrane. However, the functions of SPNS3 in acute myeloid leukemia (AML) are unknown. This study obtained SPNS3 from a gene set that was related to AML relapse and evaluate whether high SPNS3 expression induced apoptosis resistance in an AML cell line, which is consistent with the role of SPNS3 as a marker of poor prognosis in the clinic. Moreover, internal tandem duplication of FMS-like tyrosine kinase 3 (FLT3-ITD) mutation and the AC127521.1/ MIR-139/SPNS3 competing endogenous RNA axis were found to regulate SPNS3 expression. In addition, we noted that SPNS3 may play an important role in the Sphingosine-1-phosphate signal pathway that is involved in the maintenance of the AML microenvironment. These results highlight the anti-apoptosis effect of SPNS3 in AML, and the potential mechanism mediating this effect was explored through bioinformatics. Abbreviations: AML: acute myeloid leukemia; FLT3-ITD: internal tandem duplication of FMS-like tyrosine kinase 3; SPNS3: spinster homolog 3; SPNS1: spinster homolog 1; SPNS2: spinster homolog 2; GO: gene ontology; S1P: sphingosine-1-phosphate; ceRNA: competing endogenous RNA; dAML: acute myeloid leukemia at diagnosis; iAML: acute myeloid leukemia after induction chemotherapy; rAML: acute myeloid leukemia at relapse; DEGs: differentially expressed genes; BP: biological processes; CC: cellular components; MF: molecular functions; MRD: minimal residual disease; EFS: event-free survival; OS: overall survival; KEGG: Kyoto Encyclopedia of Genes and Genomes; SPHK: Sphingosine kinase.